2019
DOI: 10.1080/16078454.2019.1702304
|View full text |Cite
|
Sign up to set email alerts
|

T-lymphocyte subsets and Th1/Th2 cytokines in convalescent patients with Epstein–Barr virus-associated aplastic anemia

Abstract: Objective: The aim of this study was to analyze T-lymphocyte subsets and Th1/Th2 cytokines in convalescent patients with Epstein-Barr virus (EBV)-associated aplastic anemia (AA). Methods: Sixty AA patients were enrolled, who were in remission following immunosuppressive therapy, including 34 EBV-negative cases and 26 EBV-positive cases. Their complete blood count (CBC), T-lymphocyte subsets, Th1/Th2 cytokines were analyzed. The correlation between EBV-DNA and T-lymphocyte subsets was evaluated, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Immunoassays of the present study showed a poor immune reconstitution of high EBV-level group as reflected in profoundly lower proportion of CD4+ T cells and abnormally elevated CD8+ T cell percentage within one-year after HSCT. In line with the present study, Chen et al concluded that the EBV DNA copy number was positively correlated with the level of CD8+ T cells and IL-10, the percentage of CD4+ T cells and the ratio of CD4+/CD8+ cells were lower in the EBVpositive group than in the EBV-negative group (Chen et al, 2020). Moreover, low numbers of endogenous CD4+ T cells will in turn increase the risk of the development of EBV-associated diseases in immunosuppressed patients (Mautner and Bornkamm, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Immunoassays of the present study showed a poor immune reconstitution of high EBV-level group as reflected in profoundly lower proportion of CD4+ T cells and abnormally elevated CD8+ T cell percentage within one-year after HSCT. In line with the present study, Chen et al concluded that the EBV DNA copy number was positively correlated with the level of CD8+ T cells and IL-10, the percentage of CD4+ T cells and the ratio of CD4+/CD8+ cells were lower in the EBVpositive group than in the EBV-negative group (Chen et al, 2020). Moreover, low numbers of endogenous CD4+ T cells will in turn increase the risk of the development of EBV-associated diseases in immunosuppressed patients (Mautner and Bornkamm, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, Li et al study suggested patients with intermediate level of EBV DNA load after HSCT might reflect balanced reconstitution of host immune response and had better OS than those with high (>90000 copies/10 6 cells) or very low level (<6000 copies/10 6 cells) of cellular EBV DNA (5-year OS 90% vs 67%, p<0.03) (Li et al, 2016). T cell dysfunction plays an important role in the reactivation and replication of EBV (Chen et al, 2020). It is likely that the presence of intermediate-level of EBV DNA load presented in PBMCs and plasma is a consequence of appropriate immunosuppression, in this case, effective clearance of T cells and better engraftment can be achieved, but it could also impair the control of viral load in latent EBV-infected cells, leading to the increased EBV DNA load in PBMCs.…”
Section: Discussionmentioning
confidence: 95%
“…This may be due to the fact that the number of T lymphocyte subsets in the inflammation and cancer population is not only related to the state of the body and the severity of the disease but also to the disease Type-related. 16 This study also found that there are certain differences in CD3+, CD4+, CD8+ T cell counts and CD4/CD8 ratios between men and women in different disease groups, and women are higher than men. This may be because women have a more complex immune system than men.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies found that the imbalances of 1/ 2 cells and their cytokines are important causes of CHB [27]. However, 1 and 2 levels are strongly associated with the cytokine levels elaborated above [21]. For different CHB TCM-syndromes, as the TCM-syndrome changes, the immune responses may also be changed due to the ratios of a mean ± standard deviation.…”
Section: Discussionmentioning
confidence: 94%
“…Under the stimulation of hepatitis B antigen, cells then mainly differentiate into two subgroups, 1 and 2. 1 mainly participates in the cellular immune response by secreting interleukin-2 (IL-2) and INFc, and 2 is mainly involved in the humoral immune response by secreting interleukin-4 (IL-4), interleukin-10 (IL-10) [21].…”
Section: Introductionmentioning
confidence: 99%